2015
DOI: 10.1530/eje-14-0719
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal plasma sodium concentrations in patients treated with desmopressin for cranial diabetes insipidus: results of a long-term retrospective study

Abstract: Context and objective: Patients with cranial diabetes insipidus (CDI) are at risk of developing both hypernatraemia and hyponatraemia, due to the condition itself or secondary to treatment with vasopressin-analogues or during administration of i.v. fluids. We aimed to assess the frequency and impact of dysnatraemias in the inpatient (INPT) and outpatient (OPT) setting in desmopressin-treated CDI, comparing those with normal thirst with those with abnormal thirst. Design: The study included 192 patients with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…The risk of hyponatraemia was higher in patients with more severe DI, who needed higher doses of regular dDAVP 50. In patients with mild CDI, a starting dose of 100-200 μg orally at night is often sufficient to control nocturia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of hyponatraemia was higher in patients with more severe DI, who needed higher doses of regular dDAVP 50. In patients with mild CDI, a starting dose of 100-200 μg orally at night is often sufficient to control nocturia.…”
mentioning
confidence: 99%
“…ficiency. In Behan's study, patients with abnormal thirst were much more likely to develop significant hypernatraemia as out-patients, when compared to patients with intact thirst appreciation (20% vs 1.4%, P = 0.02) 50. The dose may be titrated until symptom control is achieved; severe disease may require up to 200 μg two to three times daily.analogues are non-suppressible.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the symptoms of polyuria and polydipsia, desmopressin is given orally or intranasally; the major complication of desmopressin therapy is hyponatraemia. A retrospective review has shown that 27% of central DI patients show mild hyponatremia (131-134 mmol/L) on routine electrolyte testing and 15% develop more severe hyponatraemia (≤130 mmol/L), over long-term follow-up 10 . Hyponatraemia develops when the antidiuretic effects of continuous desmopressin therapy prevent free water excretion, even with normal fluid intakes.…”
Section: How To Manage Patients With An Established Diagnosis Of Diabmentioning
confidence: 99%
“…-Epidemiological data show that hypernatraemia is rare in ambulatory patients with DI; in contrast, the rate of hypernatraemia during hospital admission is significant 10 . The aetiology of this hypernatraemia is multifactorial; if cognition is attenuated by critical illness, fluid intake may be reduced, and if the patient is vomiting, oral desmopressin intake may be difficult.…”
Section: Acute Infection With Suspected or Confirmed Covid-19mentioning
confidence: 99%